Analysis of Urinary Amino Acids by High-Performance Liquid Chromatography with Fluorescence Detection Using 2,3-Naphthalenedicarboxaldehyde as Fluorescence Derivatization Reagent - Yuma Ishida; Ryoto Inoue; Makoto Tsunoda (Separations, 2023)
Amino acids are involved in various chemical reactions in vivo, and changes in several amino acids in urine are related to certain disease states. Therefore, developing an efficient method to analyze the amino acids in urine is useful in the timely diagnosis of diseases. In this study, we developed a high-performance liquid chromatography (HPLC) fluorescence method for the quantitative analysis of urinary amino acids using the fluorescence derivatization reagent 2,3-naphthalenedicarboxaldehyde (NDA). NDA was selected because it does not require heating for the reaction and can react within a short time, rendering its use in clinical settings feasible. The reaction temperature, reaction time, and other derivatization conditions were optimized, and the reaction was found to be completed in 5 min at 25 °C. The separation of NDA–amino acids was investigated on an octadecylsilyl (ODS) column under gradient conditions. The mobile phase was a mixture of water–acetonitrile–trifluoroacetic acid. Eighteen NDA–amino acids (histidine (His), arginine (Arg), asparagine (Asn), glutamine (Gln), citrulline (Cit), serine (Ser), aspartic acid (Asp), threonine (Thr), glutamic acid (Glu), glycine (Gly), tyrosine (Tyr), alanine (Ala), tryptophan (Trp), valine (Val), phenylalanine (Phe), isoleucine (Ile), leucine (Leu), and 5-aminovaleric acid (internal standard)) were separated within 100 min under optimal conditions. The calibration curves showed good linearity in the range of 0.25–25 pmol per injection with correlation coefficients of >0.998. The limits of quantification for NDA–amino acids were 16.7–74.7 fmol. The developed analytical method was applied to a human urine sample and 16 amino acids (His, Arg, Asn, Gln, Cit, Ser, Thr, Glu, Gly, Tyr, Ala, Trp, Val, Phe, Ile, and Leu) were quantified. The urinary amino acid concentrations were 5–960 μM. Urinary amino acid analysis using this method is expected to be clinically applicable as a novel biomarker for diseases affecting the bladder, urinary tract, and kidneys.